Goldilocks on the couch: Moderate levels of psychodynamic and process-experiential technique predict outcome in psychodynamic therapy. (3rd May 2016) - McCarthy, Kevin S.; Keefe, John R.; Barber, Jacques P.
Abstract: Objectives: Greater symptom change is often assumed to follow greater technique use, a "more is better" approach. We tested whether psychodynamic techniques, as well as common factors and techniques from other orientations, had a curvilinear relation to outcome (i.e., whether moderate or "just right" intervention levels predict better outcome than lower or higher levels).Methods: For 33 patients receiving supportive-expressive psychodynamic psychotherapy for depression, interventions were assessed at Week 4 using the multitheoretical list of therapeutic interventions and symptoms were rated with the Hamilton Rating Scale for Depression.Results: Moderate psychodynamic and experiential techniques predicted greater symptom change compared to lower or higher levels.Conclusion: This "Goldilocks effect" suggests a more complex relation of intervention use to outcome might exist.